From Mn3O4/MnO core–shell nanoparticles to hollow MnO: evolution of magnetic properties. (5th January 2018) - Omelianchik, A; Singh, G; McDonagh, Brigitte H; Rodionova, V; Fiorani, D; Peddis, D; Laureti, S
Abstract: Manganese oxide nanoparticles (MNOPs), when dispersed in a water solution, show a magnetic behavior that drastically changes after an aging process. In this paper, the variation in the magnetic properties has been correlated with the structural evolution of the nanoparticles: in particular, the as prepared Mn3 O4 /MnO core/shell system manifests a low temperature magnetization reversal that is strongly affected by the presence of the MnO shell and, in particular, by the existence of a frustrated interfacial region playing a key role in determining the low temperature irreversibility, the finite coercivity slightly above the Curie temperature of the Mn3 O4 phase and the horizontal displacement of the FC-hysteresis loop. On the other hand, the magnetic behavior of the aged system results dominated by the presence of Mn3 O4 whose highly anisotropic character (i.e. high coercivity and high magnetization remanence) is attributed to the presence of a large fraction of surface spins. Such a result is consistent with the structural evolution, from core/shell to hollow nanoparticles, as shown by TEM observation.